Alcohol intake and periodontitis in adults aged ≥30 years: NHANES 2009–2012. Issue 6 (10th July 2018) - Gay, Isabel C.; Tran, Duong T.; Paquette, David W.
Abstract: Background: Whether an association between alcohol consumption and periodontitis exists is still unclear. This study aimed to assess the association between alcohol consumption and periodontitis. Methods: 7062 adults 30 years or older who participated in 2009–2010 and 2011–2012 cycles of the National Health and Nutrition Examination Survey (NHANES) were included. Alcohol consumption measurement included self‐reported average number of alcoholic drinks per week over the previous 12 months and was categorized into four groups (0,  < 1, 1‐ < 8, and ≥8 drinks per week). Participants were categorized using surveillance case definitions for periodontitis that included both clinical attachment level (CAL) and periodontal probing depth (PD) measurements. The association between alcohol consumption and chronic periodontitis was evaluated by multivariable regression analyses adjusting for age, gender, race/ethnicity, education level, income‐to‐poverty ratio, smoking, self‐rated overall oral health, and HbA1c . Results: The odds ratio (95% confidence interval) of having severe periodontitis was 1.9 (1.2‐3) among participants who reported alcohol consumption of ≥8 drinks compared to participants consuming some alcohol but < 1 drink per week on average. Participants who consumed 1‐ < 8, and ≥8 drinks per week, on average, also had higher mean PD, percentage of sites with PD ≥4 mm, mean CAL, and percentage of sites with CAL ≥3 mm compared to participants reporting consumption of < 1 drink per week. Meanwhile, the odds of having periodontitis, mean PD, extent PD ≥4 mm, mean CAL, and extent CAL ≥3 mm were not significantly different for nondrinkers than for participants who consumed some alcohol but < 1 drink per week on average. Conclusions: Alcohol consumption was associated with an increase in the likelihood of having periodontitis, particularly severe periodontitis. Consumption of some alcohol,  < 1 drink per week on average, was associated with similar odds of having periodontitis compared to consumption of no alcohol.